Energy Efficiency of Residential Buildings in the European Union – An Exploratory Analysis of Cross-Country Consumption Patterns - Anita Thonipara; Petrik Runst; Christian Ochsner; Kilian Bizer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2018)
Despite a common EU directive on energy efficiency in residential buildings, levels of energy efficiency differ vastly across European countries. This article analyses these differences and investigates the effectiveness of different energy efficiency policies in place in those countries. We firstly use panel data to explain average yearly energy consumption per dwelling and country by observable characteristics such as climatic conditions, energy prices, income, and floor area. We then use the unexplained variation by sorting between-country differences as well as plotting within-country changes over time to identify better performing countries. These countries are analysed qualitatively in a second step. We conduct expert interviews and examine the legal rules regarding building energy efficiency. Based on our exploratory analysis we generate a number of hypotheses. First, we suggest that regulatory standards, in conjunction with increased construction activity, can be effective in the long run. Second, the results suggest that carbon taxation represents an effective means for energy efficiency.
Keywords: H23; K32; P18; Q58; 330; carbon-taxation; energy efficiency; energy conservation; climate policy; residential buildings